2018
DOI: 10.1029/2017jd028205
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Observed Electrical Effect on the Raindrop Size Distribution in Tropical Clouds

Abstract: In the backdrop of extensive laboratory and theoretical evidence of broadening of the drop size distribution (DSD) of raindrops in the presence of electric field, quantification of the same in observed tropical clouds is lacking. Here this is quantified using the DSD measured by a microrain radar at 2,400‐, 1,200‐, and 600‐m heights from the surface in six strongly electrified and six weakly electrified stratiform rain events together with the DSD of raindrops at the surface measured by a disdrometer for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 60 publications
(112 reference statements)
0
9
0
2
Order By: Relevance
“…The underestimation of rainfall in the model for deep convective clouds in the presence of a strong electric field might be related to the underestimation of raindrop size distribution (RDSD) as reported by Mudiar et al . ().…”
Section: Resultsmentioning
confidence: 97%
“…The underestimation of rainfall in the model for deep convective clouds in the presence of a strong electric field might be related to the underestimation of raindrop size distribution (RDSD) as reported by Mudiar et al . ().…”
Section: Resultsmentioning
confidence: 97%
“…The electrical characteristics of the four rain events chosen for the simulation experiments are ascertained by the presence/absence of lightning discharges in the innermost model domain. Lightning data from the World Wide Lightning Location Network (WWLLN) with a detection efficiency of 25%-30% for cloud to ground flashes (CG) (Mudiar et al,2018) and the Maharashtra Lightning Location Network (MLLN) with a detection efficiency of about 90% for CG (Greeshma et al, 2021) are analyzed in this study. Some of the available cloud properties of the four storms derived from the MODIS collection 6 (Baum et al, 2012) and ERA5 at 0.25° × 0.25° resolution MUDIAR ET AL.…”
Section: Model Data and Methodologymentioning
confidence: 99%
“…However, recent investigations on the raindrop size distribution (RDSD) in tropical SE cloud brings out another intriguing explanation of the presence of larger drops in this fraction of cloud. In a series of papers, Mudiar et al (2018), (Mudiar, Pawar, Hazra et al, 2021, Mudiar, Pawar, Gopalakrishnana et al, 2021 have shown that the prevailing stronger electric environment inside the SE cloud can facilitate the production of larger raindrops at the surface. They have shown that the cloud electric field can efficiently induce coalescence growth of the raindrops, thereby producing larger raindrops.…”
mentioning
confidence: 99%
“…In a case study approach, Mudiar et al. (2018) utilized lightning network observations to delineate the presence of higher concentration of bigger raindrops in strongly electrified storms owing to enhancement in collision‐coalescence processes over the WG. Theoretical studies by Davis (1964) and Schlamp et al.…”
Section: Introductionmentioning
confidence: 99%
“…The advection of moisture laden south-west monsoon winds, heated land surface (Kamra & Ramesh Kumar, 2021) accompanied by strong updrafts across complex topography (Vishnu et al, 2013) are the major causes of lightning over the mesoscale mountain ranges of Western Ghats (WG). In a case study approach, Mudiar et al (2018) utilized lightning network observations to delineate the presence of higher concentration of bigger raindrops in strongly electrified storms owing to enhancement in collision-coalescence processes over the WG. Theoretical studies by Davis (1964) and Schlamp et al (1976Schlamp et al ( , 1979 have shown that strong electric fields and surface charges of raindrops inside the cloud can increase the coalescence efficiency upon collision between the drops.…”
mentioning
confidence: 99%